Development of a MSMEs Digitalization Transformation Model: Optimization of The Use of Crowdfunding as an Alternative to Information Technology Based Capital Solutions - Zulfahmi; Ngarbingan, Hubertina Karolina; Ginting, Ginta; Ismulyati, Sri; Nasoha, Mohamad (Yayasan Sinergi Kawula Muda, 2024)
Digitalization of MSMEs is one strategy to accelerate the development of MSMEs in an inclusive and massive manner. The Financial Technology (Fintech) phenomenon in recent years has encouraged the emergence of various new services in the financial sector, including Crowdfunding. Crowdfunding is the practice of raising funds or investment by utilizing a site or website. Currently, it is indicated that there is still very little use of crowdfunding among MSMEs players. For this reason, a comprehensive study is needed regarding the importance of MSMEs utilizing Crowdfunfing as an alternative to overcome capital problems. Research design used is mix method (descriptive non experimental and judgement sampling). Sample are selecting by non-random sampling (judgment sampling). Based on the results of a survey involving 71 business doers, most of them are managers and owners, included the category of small and medium business doers with 50 to 100 employees, it was found that most of these business doers were familiar with crowdfunding as an easily accessible funding alternative. The results of the analysis using SEM-PLS, interesting findings were obtained that perceptions and aspects of technology and entrepreneurship from business actors had a positive effect on interest in using crowdfunding. Recommendations for future research are the need to research the role of capital markets and regulations, which in this research were assessed as having not been optimally socialized by MSMEs players. The point is that in the future MSMEs players must be given space to gain access to funding through crowdfunding in an inclusive manner.